A series of Keggin-based AgI-belt/cycle structures constructed from 5-phenyl-1H-tetrazole and its derivative through Ag–N and Ag–C bonds. Issue 3 (1st February 2017) - Tian, Ai-Xiang; Ji, Xue-Bin; Xiao, Ru; Ni, Huai-Ping; Tian, Yan; Liu, Guo-Cheng; Ying, Jun
Abstract: Three Keggin-based compounds containing Ag I belts and cycles constructed from 5-phenyl-1H-tetrazole (L 1 ) and its derivative 5-m-tolyl-1H-tetrazole (L 2 ), [Ag9 L 1 5 (PW V W VI 11 O40 )]·H2 O (1 ), [Ag11 L 1 6 (H2 O)2 (SiMo V Mo VI 11 O40 )] (2 ) and [Ag10 L 2 8 (HPMo12 O40 )]·H2 O (3 ), have been synthesized under hydrothermal conditions and characterized by IR spectra and single crystal X-ray diffraction. Compound1 shows a channel-like 3-D metal-organic framework with Keggin anions in channels. Adjacent layers of2 share the same anions to construct a 3-D framework. Compound3 has a 2-D metal-organic layer containing Ag I cycles. Adjacent layers link through sharing Ag–N bonds and a channel-like 3-D framework is formed. Electrochemical and photocatalytic properties of1 –3 have been studied. The experimental results show that1 –3 have excellent catalytic performance for reduction of nitrite and bromate and also have photocatalytic properties for degradation of MB and RhB. Abstract :